Philosophical Framework To Intellectual Capital Readiness in Iraqi Organizations - حمود سعد علي; هاشم صبيحة قاسم; شياع حسام حسين (Journal of Economics and Administrative Sciences, 2014)
This research aim to present theoretical and philosophical framework regards topic of intellectual capital readiness in Iraqi universities. That is, by using strategic map in balanced score card of Norton and Kaplan (2004). This research discusses theoretical content for three main aspects reflect in its nature elements of intellectual capital readiness in organizations. This includes human capital readiness, information capital readiness and organizational capital readiness. To clear each element, the authors relay on mechanism to determine gape per element of intellectual capital elements.